Mapping High School Students' Metacognition Based On Mathematics Skills - Santoso, Hajar Ahmad; Istiqomah, Nisa Rachmi; Santoso, Digdo (Journal of Mathematical Pedagogy (JoMP), 2021)
Problem solving and metacognitive are two things that are interrelated. Problem solving is synonymous with cognitive processes whereas metacognition is synonymous with controlling and regulating cognitive processes. This study aims to describe the metacognition of students with different mathematical abilities. The subjects in this study consisted of one student with high, medium, and low math abilities. Data analysis was carried out based on metacognition indicators and problem solving. It was found that, there were differences in the three subjects in solving problems. The three subjects were able to fulfill the three components of metacognition, namely awareness, regulation, and evaluation. From this study, it is suggested to conduct a deeper assessment of the metacognition process of students with high, medium, and low math abilities to see their characteristics.